Trees for brains: current residential tree cover density and its association with brain structure in young adults - Kühn, Simone; Banaschewski, Tobias; Bokde, Arun L. W.; Büchel, Christian; Burke Quinlan, Erin; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Gowland, Penny; Heinz, Andreas; Ittermann, Bernd; et al. (Journal of environmental psychology, 2023)
Previous research has suggested an association between living environment during the first 15 years of life and brain structure. More precisely, urbanicity during upbringing has been shown to be negatively related to prefrontal cortex grey matter. The present study focusses instead on the current living environment of 677 younger adults recruited from different cities across Europe. We observed a positive association between amount of tree cover density, in a radius of 500m around the current home address and grey matter volume in right orbitofrontal cortex (rOFC). Of note, the volume of the rOFC cluster identified, showed a positive association with cognitive performance in the Wechsler Adult Intelligence Scale, namely in the verbal and spatial ability domain (Vocabulary, Block Design), and a negative association with both, self-reported and behavioural markers of impulsivity (delay discounting). Moreover, rOFC volume showed a negative association with self-reported alcohol use problems. The data provide strong evidence in favour of a link between geographical features of the current living environment (particularly trees) and brain structure above and beyond childhood and upbringing. Interestingly, the respective brain correlates are associated with cognitive, behavioural and personality characteristics which have been considered as risk factors for several psychiatric disorders. Environmental neuroscience may in the long run provide a knowledge base for evidence-based urban landscape planning to facilitate mental health.